Developing a Virtual Laboratory on Computer Assembly to Improve SMK Students’ Motivation and Independent Learning Skills Using the ADDIE Model - Paat, Wensi Ronald Lesli; Kamasi, Nadya Verona Viani; Ratumbuisang, Keith Francis; Modeong, Merriam Listiany (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Students' motivation for independent learning remains low, partly due to the lack of engaging and high quality learning media. This study aims to develop a virtual laboratory for computer assembly to support high school students’ independent learning. The virtual lab was developed using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observation, interviews, and questionnaires based on the ISO 25010 instrument. Evaluation involved two media experts and ten users (two teachers and eight students), yielding feasibility scores of 110.08 and 111.8, both rated “Very Feasible.” A small-group trial with 60 students (experimental and control groups) showed a significant difference in learning outcomes (t-test sig. = 0.000), with the experimental group scoring higher (M = 51.79) than the control group (M = 36.67). These results suggest that the virtual lab has the potential to enhance students' independent learning abilities in the short term. However, caution is needed in interpreting these results, as other factors such as novelty effects, teacher influence, or students’ prior knowledge may also have contributed.